2021
DOI: 10.11648/j.rst.20210702.13
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Assessment of Occupational Exposure to Solar Ultraviolet Radiation in Makurdi Metropolis, Benue State, Central Nigeria

Abstract: This work measured and modeled Ultraviolet (UV) Radiation exposure of outdoor workers (Traders, Drivers/Commuters and Construction workers) within Makurdi Metropolis. Digital broad band meter was used to measure Irradiance across the three occupations under consideration. Polymer Polysolphone dosimeters were used to quantify the amount of solar UVR absorbed by workers of these occupations, UV/VIS-Spectrophotometer was used to measure both post and pre-absorbance while GPS was used to measure the coordinate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…UV radiation is one of the most important physical concerns in the workplace. As is always the case with agricultural and construction jobs, both governmental and non-governmental organizations anticipate workers to perform their daily tasks during the middle of the day and/or during the dry seasons; this period, the intensity of the radiation from the sun is always very high (Sombo et al, 2021). Market locations, parking lots, farmlands, playgrounds and job sites in rural areas with little or no ultraviolet protection are where the risk is greatest (Tertsea et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UV radiation is one of the most important physical concerns in the workplace. As is always the case with agricultural and construction jobs, both governmental and non-governmental organizations anticipate workers to perform their daily tasks during the middle of the day and/or during the dry seasons; this period, the intensity of the radiation from the sun is always very high (Sombo et al, 2021). Market locations, parking lots, farmlands, playgrounds and job sites in rural areas with little or no ultraviolet protection are where the risk is greatest (Tertsea et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Market locations, parking lots, farmlands, playgrounds and job sites in rural areas with little or no ultraviolet protection are where the risk is greatest (Tertsea et al, 2013). Humans are exposed to UV rays in different ways depending on their activities, body posture, personal conduct, and use of UV protection equipment (Sombo et al, 2021). Since the advent of modern epidemiology, numerous authors have shown a connection between solar UV radiation and cataract, specifically between UV-B radiation and cortical cataract (Löfgren, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ultraviolet radiation (UV) is divided into three bands of wavelengths, which are UVA (320-400nm), UVB (290-320nm) and UVC (200-290nm) [3]. A major portion of the UVA and about 10% of UVB radiation reaches the earth's surface from the sun while UVC is totally absorbed by the atmospheric ozone, water vapour and gasses [4,2,5].…”
Section: Introductionmentioning
confidence: 99%